Factors associated with incomplete latent tuberculosis infection preventive treatment in Sabah, Malaysia - Ahmad Firdaus Mohamed; Mohd Nazri Shafei; Wan Mohd Zahiruddin Wan Mohammad; Roddy Teo; Amabel Seow Min Hui (PeerJ)
Background Latent tuberculosis infection (LTBI) is a critical public health issue in Malaysia, particularly in regions like Sabah, where the incidence of tuberculosis (TB) remains high. LTBI can progress to active TB if left untreated, making preventive treatment essential in reducing TB transmission. However, adherence to LTBI preventive treatment remains a significant challenge, with incomplete treatment potentially undermining efforts to control TB. This study aimed to determine the proportion of individuals with LTBI who did not complete preventive treatment and to identify associated factors. Methods A retrospective record review was conducted among individuals with LTBI registered in the Sabah State Health Department’s LTBIS 401A registry. Multiple logistic regression analyses were applied to determine the factors associated with incomplete preventive treatment. Results A total of 895 individuals with LTBI were included in the study. The proportion of incomplete LTBI preventive treatment was 9.2%. Factors that were significantly associated with the incomplete preventive treatment were non-HCW occupation (adj.OR = 4.21, 95 CI [1.25–14.22]), residents of Tawau Division (adj.OR = 2.00, 95% CI [1.10–3.65]), and individuals with LTBI without contact to TB patients (adj.OR = 2.79, 95% CI [1.42–5.48]). Conclusion The proportion of incomplete preventive treatment among individuals with LTBI in Sabah was comparatively lower than many previous studies. Targeted interventions should be developed to address the specific needs of the groups with higher odds of having incomplete preventive treatment. It includes tackling the social determinants of health, like improving healthcare system accessibility. A prospective study to evaluate these interventions’ effectiveness in improving preventive treatment completion rate is recommended.